Advances in the development of amorphous solid dispersions: The role of polymeric carriers - Jie Zhang; Minshan Guo; Minqian Luo; Ting Cai (Elsevier, 2023)
Amorphous solid dispersion (ASD) is one of the most effective approaches for delivering poorly soluble drugs. In ASDs, polymeric materials serve as the carriers in which the drugs are dispersed at the molecular level. To prepare the solid dispersions, there are many polymers with various physicochemical and thermochemical characteristics available for use in ASD formulations. Polymer selection is of great importance because it influences the stability, solubility and dissolution rates, manufacturing process, and bioavailability of the ASD. This review article provides a comprehensive overview of ASDs from the perspectives of physicochemical characteristics of polymers, formulation designs and preparation methods. Furthermore, considerations of safety and regulatory requirements along with the studies recommended for characterizing and evaluating polymeric carriers are briefly discussed.